The Image of woman in the poetry of kareem Al-Iraqi an analytical interpretive study a research paper extracted from a master`s thesis - Abdulrahman, Master`s student: Dlxwaz Mohammed Abdulrahman; Karim, Prof.Dr. Dahir Latif Karim (Sulaimani Journal for Humanities, 2025)
The portrayal of women in modern Arabic poetry marks a clear departure from traditional representations.in this contemporary phase women are seen through a renewed lens- one shaped by evolving thought broader vision and a growing sense of awareness poets now call for women’s freedom and highlight their social and intellectual presence moving away from portrayals rooted in superficial or purely physical appeal.
Keywords: Woman; Modern Arabic Poetry; Kareem Al Iraqi